The Psychological Conditions of Mother and Child Survivors on West Lombok Post-Earthquake - Dewi Puri Astiti; IGA Diah Fridari; Putu Nugrahaeni Widiasavitri; , Supriyadi (Journal of Psychology and Instruction, 2019)
Earthquake survivors have physical and psychological effects. Survivors of the earthquake in Lombok in July 2018 then still caused a considerable psychological impact, one of which was post-earthquake trauma or PTS. Since the post-earthquake, earthquake survivors have tried to live their lives, but of course earthquake survivors have not completely overcome the psychological problems experienced after the earthquake. Post-earthquake psychological conditions require psychosocial treatment to be resolved, an indication of high anxiety, stress or depression will result in a more acute psychological condition. Screening is needed related to the description of the psychological condition of mothers and children of earthquake survivors in order to find out the problems that occur in the field and can be preliminary data to find solutions related to the psychological problems of earthquake survivors. This study uses quantitative methods by selecting respondents as mothers and children under the age of 9 years as survivors of the 2018 Lombok earthquake. The initial screening used 163 mothers who were given with DASS (Depression, Anxiety and Stress Scale) and 163 children given the Screening for Scale Child Anxiety Related Disorder (SCARED). The results from the statistical analysis further reveal was found that the psychological condition that still appeared was anxiety, 53 mothers were at the level of severe and very severe anxiety while the child felt anxious separation from the mother by 109 and as many as 54 remaining were still experiencing general anxiety due to the earthquake.